Prevalence, awareness and risk factors of hypertension in Hmawbi Cantonment Area, Yangon Region, Myanmar (South East Asia Journal of Public Health, 2016)
Hypertension is one of the leading risk factors for global mortality. A community based cross sectional descriptive study was conducted in Hmawbi Cantonment Area, Yangon Region in November, 2015. This study aimed to identify the prevalence, awareness and risk factors of hypertension concerning smoking, alcohol dinking, eating food pattern, taking regular exercise, stressful condition and body mass index (BMI). The sample consisted of 210 respondents from three Units (Light Infantry Regiments) were randomly selected to participate in the study. A pre-tested structured questionnaire was used as a data collection tool. It was found that 33.3% of respondents had hypertension; 55.7% achieved good awareness on hypertension as well; 16.7% respondents were current smoker; 7.6% had the history of alcohol drinking; 67.1% respondents took regular exercise; 29.5% respondents were in stressful condition; 32.9% re-spondents were overweight and 19.5% were obese. Hypertension was significantly associated with age (p-0.001), family income (p